Modulation of Crustacean Innate Immune Response by Amino Acids and Their Metabolites: Inferences From Other Species - Huang, Zishu; Aweya, Jude Juventus; Zhu, Chunhua; Tran, Ngoc Tuan; Hong, Yujian; Li, Shengkang; Yao, Defu; Zhang, Yueling (Frontiers in Immunology, 2020)
Aquaculture production of crustaceans (mainly shrimp and crabs) has expanded globally, but disease outbreaks and pathogenic infections have hampered production in the last two decades. As invertebrates, crustaceans lack an adaptive immune system, and mainly defend and protect themselves using their innate immune system. The immune system derives energy and metabolites from nutrients, with amino acids constituting one such source. A growing number of studies have shown that amino acids and their metabolites are involved in the activation, synthesis, proliferation and differentiation of immune cells, as well as in the activation of immune related signaling pathways, reduction of inflammatory response and regulation of oxidative stress. Key enzymes in amino acid metabolism have also been implicated in the regulation of the immune system. Here, we reviewed the role played by amino acids and their metabolites in immune-modulation in crustaceans. Information is inferred from mammals and fish where none exists for crustaceans. Research themes are identified and the relevant research gaps highlighted for further studies.